Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1159/000046972
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hypoalbuminemia on Maximal Flow Rates and Transmembrane Pressure during Plasmapheresis – An in vitro Study

Abstract: Background: Plasmapheresis has been used for the treatment of acute liver failure (ALF). In these patients, hypoalbuminemia is often observed. Since albumin improves the disaggregability of erythrocytes, hypoalbuminemia might deteriorate rheology and thus influence the overall performance of plasmapheresis. Methods: Hypoalbuminemia was mimicked by using porcine blood because of its physiologically low albumin/globulin ratio (AGR). Filters (n = 16) were integrated in a closed extracorporeal in vitro system. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…In particular, unfavorable hemorheological conditions are given because of a low ALB/globulin ratio and a very low hematocrit level. Both aspects are highly supportive for increased blood cell aggregability and hemofilter blockage (19,24,25). A low stress resistance of the right ventricular function in pigs is given as a partly neglected side effect of breeding programs exclusively focused on special preferences in food consumption.…”
Section: Experimental Model and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, unfavorable hemorheological conditions are given because of a low ALB/globulin ratio and a very low hematocrit level. Both aspects are highly supportive for increased blood cell aggregability and hemofilter blockage (19,24,25). A low stress resistance of the right ventricular function in pigs is given as a partly neglected side effect of breeding programs exclusively focused on special preferences in food consumption.…”
Section: Experimental Model and Protocolmentioning
confidence: 99%
“…However, we have shown that cell aggregation in convection-based membrane processes is a main problem (18,19). Increased blood cell aggregation may lead to a reduced blood flow velocity and cessation of blood flow within the hollow fibers, which in turn automatically accelerates hemostasis and increases the overall activation of the coagulation system.…”
Section: Introductionmentioning
confidence: 99%
“…HES 130/0.4 is known to reduce RBC aggregability. These findings are paralleled by the observation that substitution of both—ALB and HES 130 kD/0.4—increases blood sedimentation rates .…”
Section: Fifth Step: Different Colloids Impact On the Biocompatibilitmentioning
confidence: 69%
“…We questioned whether or not the impaired hemorheology in critically ill patients (hyperaggregability due to changes in blood cell counts, impaired RBC features after transfusion, or decreases in the AGR) may be a dominant reason for unfavorable flow dynamics in the filters' hollow fibers and, in turn, the main reason for filter “clotting” . Histopathological examinations of the capillary membranes of plasmafilters, which were operated in our in vitro system, revealed extensive RBC aggregates as the main reason for blocked hollow fibers (Fig.…”
Section: Second Step: the Impact Of Red Blood Cell (Rbc) Aggregabilitmentioning
confidence: 95%
“…For in vivo it is also described that crystalloids and colloids aect rheological properties in a dierent manner [13]. Using a specially established in vitro system, we found that the solutions, which are chosen for volume replacement, in¯uence pressure pro®les and hemocompatibility of the plasmaseparation procedure based on capillary membrane ®lters [14,15].…”
Section: Introductionmentioning
confidence: 93%